Nondestructive Inspection of Thin Basalt Fiber Reinforced Composites Using Combined Terahertz Imaging and Infrared Thermography - Przemyslaw Lopato; Grzegorz Psuj; Barbara Szymanik (Advances in Materials Science and Engineering)
The inspection of thin basalt fiber reinforced composite materials was carried out using two nondestructive methods: terahertz time domain imaging and infrared thermography. In order to combine the information about the defects arising in examined materials the inspection results were parametrized. In order to acquire more information content, new approximation based features are proposed. Then, a knowledge extraction based multivariate analysis of preselected features’ vector was carried out. Finally, in order to integrate features distributions of representing different dynamic level of information, a multiresolution wavelet based data fusion algorithm was applied. The results are presented and discussed.